Very large amplitude vibrations of flexible structures: Experimental identification and validation of a quadratic drag damping model. (August 2020) - Colin, Mathieu; Thomas, Olivier; Grondel, Sébastien; Cattan, Éric
Abstract: This article presents a theoretical, numerical and experimental study of resonant structures undergoing very large amplitude vibrations. The purpose of this work is to validate a model for the damping due to the action of the air on a structure's single-mode response in the steady-state. Experiments are performed on cantilever beams and beam assemblies of various sizes, from centimetric to micrometric, under harmonic base excitation. Dimensionless linear and nonlinear modal damping coefficients are simultaneously identified by means of frequency-domain identification techniques. These measurements demonstrate the pertinence of the presented model. Highlights: We propose a model and an identification technique for nonlinear damping. It applies to thin structures in large amplitude vibrations. It is based on a modal damping term quadratic in the velocity due to fluid interaction. Identification technique is validated on numerical simulations. Model validated by experiments on structures of various sizes in the frequency domain.